Advanced multi-step security scheme using PCA for RFID system and its FPGA implementation. (2015) - Bag, Joyashree; Roy, Subhashis; Kantha, Bijoy; Sarkar, Subir Kumar
Security of stored data within a RFID tag and the data transmission process is important to both the designer and the user. The application of RFID in various domains is increasing owing to its ease of use, flexibility, low cost and enormous advantages of quick accessing and data transfer technology. Those deployments have a risk of unauthorised access to sensitive biometric or financial information through the tag communication. In this paper, programmable cellular automata (PCA) have been used to achieve a multi-step security for an RFID system. The proposed scheme has high level of security, as it provides step by step encryption with different keys and PCA rules for each part. The complexity of the circuit is reduced significantly by reducing the hardware size and power dissipation to a minimum level. The processor for reader and tag frame generator has been developed and implemented using Xilinx ISE14.3 simulation tools and Kintex™-7 FPGA board.